NOVEL ATHEIS KARYA ACHDIAT KARTA MIHARDJA SEBAGAI MATERI PEMBELAJARAN SASTRA : ANALISIS PSIKOLOGI SASTRA DAN NILAI PENDIDIKAN - Haryo Seto Saktiyono; Herman J Waluyo; Sri Hastuti (Universitas Sebelas Maret, 2018)
The objectives of this research is to describe: (1) id psychology on the main character in Atheis novel by Achdiat Karta Mihardja; (2) ego psychology on the main character in the Atheis novel; (3) super-ego psychology on the main character in the Atheis novel; (4) the educational value contained in the Atheis novel; (5) its relevance as teaching material in learning literature appreciation in high school.This research uses descriptive qualitative method with psychology approach of literature. This research uses descriptive qualitative method with psychology approach of literature. The data obtained by researchers coming from Atheis novel, interviews with writers, lecturers of Indonesian language studies program, teachers and students. The validity of data is obtained through triangulation theory. Data were analyzed using analysis techniques interactive.The conclusions of this study were (1) the psychology of the main character in the Atheis novel by Achdiat Karta Mihardja is a Hasan character who suffers from psychiatric disorder that is the uncertainty of choosing religious belief (2) there are eleven grades of character traits contained in Atheis novel, they are religious values, tolerance, hard work, social caring, curiosity, friendship, responsibility, self-reliance, peace, discipline, like to read (3) Atheis novel is relevant to the literary learning material in senior high school because it contains many moral messages and good character education value for students.